Peran Bahasa Indonesia Dalam Pengelolaan Komunikasi Organisasi - Fadia Aprillia; Anggi Siagian; Cipta Kurnia; Arkhan Hafidz Purba; Nabila Khairunnisa; Yeny Elfina; Syairal Fahri Dalimunthe (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study discusses the role of Indonesian as an important tool in managing organizational communication. In the context of social and cultural development, Indonesian not only functions as a medium of communication but also as a national identity that strengthens the character of the younger generation. Through existing literature which emphasizes the contribution of language in building character, as well as other works that show how language plays a role in interpersonal interactions and cultural identity, this article explores the importance of using good and correct Indonesian in organizational communication. This study emphasizes that effective mastery of Indonesian in an organizational environment can increase productivity and team cohesion, while strengthening the identity and cultural values of the nation in the digital era.